Ways to increase the sensitivity of line protection during abnormal operation on branches with low-power transformers - Gilmanov R. R. (Science, education, society: trends and prospects, 2023)
This article discusses various ways to solve the problem of recognizing short-circuit currents at various abnormal operating modes on branches with low-power transformers. The following options for solving this problem will be considered: a method for increasing the sensitivity of distance protection lines to two-phase short circuits; operability of protection of long-range redundancy of transformers under the condition of longitudinal-transverse asymmetry; implementation of a distance protection stage using information about the currents from the supply ends of the branch line
Keywords: protection; короткие замыкания; Branch line; short circuits; sensitivity; distance protection; long-range redundancy; phase-to-phase short circuits; low power transformers; линия с ответвлениями; дальнее резервирование; междуфазные короткие замыкания; маломощные трансформаторы